2010
DOI: 10.4103/1658-354x.71573
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of esmolol and labetalol, in low doses, for attenuation of sympathomimetic response to laryngoscopy and intubation

Abstract: Objective:The present study compared the efficacy of esmolol and labetalol, in low doses, for attenuation of sympathomimetic response to laryngoscopy and intubation.Design:Prospective, randomized, placebo controlled, double-blinded study.Setting:Operation room.Patients and Methods:75 ASA physical status I and II adult patients, aged 18-45 years undergoing elective surgical procedures, requiring general anesthesia and orotracheal intubation.Interventions:Patients were allocated to any of the three groups (25 ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 20 publications
4
32
0
2
Order By: Relevance
“…lidocaine, opioids, inhaled anesthetics, vasodilators, calcium channel blockers or adrenergic blockers have been used successfully for decreasing the hemodynamic response to laryngoscopy. [2][3][4][5][6][7] Esmolol is a water soluble, rapid onset, ultra-short-acting, selective β adrenergic receptor antagonist with proven efficacy to provide hemodynamic stability during laryngoscopy and tracheal intubation. 2 It has a half-life of nine minutes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…lidocaine, opioids, inhaled anesthetics, vasodilators, calcium channel blockers or adrenergic blockers have been used successfully for decreasing the hemodynamic response to laryngoscopy. [2][3][4][5][6][7] Esmolol is a water soluble, rapid onset, ultra-short-acting, selective β adrenergic receptor antagonist with proven efficacy to provide hemodynamic stability during laryngoscopy and tracheal intubation. 2 It has a half-life of nine minutes.…”
Section: Introductionmentioning
confidence: 99%
“…lidocaine, opioids, inhaled anesthetics, vasodilators, calcium channel blockers or adrenergic blockers have been used successfully for decreasing the hemodynamic response to laryngoscopy. [2][3][4][5][6][7] Esmolol is a water soluble, rapid onset, ultra-short-acting, selective β adrenergic receptor antagonist with proven efficacy to provide hemodynamic stability during laryngoscopy and tracheal intubation.2 It has a half-life of nine minutes.Dexmedetomidine is an imidazole derivative and selective alpha α2 adrenergic receptor agonist. 8 α2-agonists produce hyperpolarization of noradrenergic neurons and suppression of neuronal firing in the locus ceruleus which leads to decreased systemic noradrenaline release resulting in attenuation of sympathoadrenal responses and hemodynamic stability during laryngoscopy and tracheal intubation.…”
mentioning
confidence: 99%
“…Montazeri et al [25] observed similar results with 800 mg gabapentin, especially on systolic, diastolic, and MAPs. Singh et al [18] found labetalol 0.25 mg/ kg more effective than esmolol 0.5 mg/kg for the attenuation of pressor response when given to patient 1 h before intubation. Chung et al [16] demonstrated that intermediate dose of labetalol blunts HR response to laryngoscopy and intubation in healthy patients but has minimal effect on BP, and in our study, the combination of labetalol and gabapentin blunted HR response better than gabapentin alone.…”
Section: Discussionmentioning
confidence: 99%
“…Roelofse et al [17] found labetalol 1 mg/kg more effective when compared with acebutolol 0.25 mg/kg and lidocaine 2 mg/kg for attenuation of pressor response. Singh et al [18] found labetalol 0.25 mg/kg more effective than esmolol 0.5 mg/kg for attenuation of pressor response when given to patient 1 h before intubation. Gabapentin is a relatively new drug, which was introduced as antiepileptic but proved to be effective in controlling neuropathic pain.…”
mentioning
confidence: 99%
“…Labetalol due to its peripheral vasodilation property does not affect the cardiac output [8]. Labetalol has been shown to have an effect on blunting the hemodynamic response to tracheal intubation [9][10][11]. Thus, we hypothesized that labetalol while blunting the hemodynamic response to tracheal intubation will not lengthen the time to onset of action of rocuronium.…”
Section: Introductionmentioning
confidence: 99%